Physical properties, antioxidant capacity, and starch digestibility of cookies enriched with steam-exploded wheat bran - Kong, Feng; Li, Yue; Xue, Di; Ding, Yishuai; Sun, Xiaofan; Guo, Xingfeng; Wang, Wenhao (Frontiers in Nutrition, 2022)
Wheat bran-based food is rich in bioactive compounds, and steam explosion enhances the nutritional properties of wheat bran. This study examined the potential utilization of steam-exploded wheat bran (SWB) in cookie formulation. The influence of steam explosion on the chemical compounds in wheat bran and the effects of SWB on the physical properties, antioxidant capacity, and starch digestibility of cookies were investigated. The results showed that steam explosion facilitated the release of reducing sugar, flavonoids, phenolic substances, and amino acid nitrogen in wheat bran, thereby improving its nutritional properties. The reduction of sugar, total flavonoids, total phenolics, and amino acid nitrogen contents of wheat bran after steam explosion increased by 34.22, 183.02, 284.09, and 93.39%, respectively, compared with those of native wheat bran. Substitution of SWB for wheat flour mainly induced higher water, sodium carbonate, and sucrose solvent retention capacities, which were positively related to the spread ratio and hardness of cookies. The cookies with more SWB substitution (30–50%) expressed a higher spread ratio and harder texture than the others. The substitution of SWB caused changes in the antioxidant properties of cookies, which were related to the phenolic content. The cookies with SWB showed a higher DPPH radical scavenging activity (16.30–30.93%) than that of the control (14.74%). SWB might form a matrix barrier to hinder starch digestion, thus reducing the digestibility of cookies. The cookies enriched with 30–50% of the SWB exhibited greater physical properties and antioxidant capacity but lower starch digestibility than those of other cookies. The results will contribute to expanding the application range and improving the quality of bran-rich flour products.